Maternal Socioeconomic Status and Fertility Behaviour in Nigeria: Evidence from a Cross Sectional Nationally Representative Survey - Obiyan, Mary O.; Akinlo, Ambrose; Ogunjuyigbe, Peter O. (European Scientific Journal, ESJ, 2019)
Aims: Studies have linked individual factors such as education and household variables including wealth index as predictors of fertility behaviour. This study aims to examine the effect of socioeconomic characteristics on fertility behaviour when combined as a single proxy among women of reproductive ages in Nigeria. Methods: Data for this study was extracted from the Nigeria Demographic and Health Surveys (NDHS) of 2003, 2008, and 2013. The explanatory variable, “socioeconomic status”, was derived as a composite index from the combination of individual and household variables. The outcome variable “fertility behaviour” is measured by total children ever born (CEB). Pearson chi-square test was used to determine the association among variables. Ordinal logistic regression was used to assess the effect of the explanatory variable on the outcome variable. Level of significance was determined at 5% and 95% confidence interval. The analysis was carried out using Stata 14.0. Results: There is a statistically significant but inverse association between socioeconomic status and reported CEB. If women were to change their socioeconomic status from low to high, the CEB would reduce by -0.502 (p<.001) and by -1.038 (p<.000). This pattern remained consistent in the adjusted model and across all surveys. Conclusion: The study concludes that women’s socioeconomic status significantly predicts fertility behaviour. An improved socioeconomic status would reduce reported CEB. Efforts to reduce fertility in Nigeria must embrace a multi-dimensional approach that creates opportunities aimed at promoting women’s economic status.